Prediction models with categorical data in psychological research via the statistical methods of prediction analysis and logistic regression - Κιοσέογλου Γρηγόρης (Psychology: the Journal of the Hellenic Psychological Society, 2020)
ABSTRACT IS AVAILABLE IN THE PDF